Transmission reduction and prevention with HPV vaccination (TRAP-HPV) study protocol: a randomised controlled trial of the efficacy of HPV vaccination in preventing transmission of HPV infection in heterosexual couples - François Coutlée; Mariam El-Zein; Pierre-Paul Tellier; Aaron MacCosham; Ann N Burchell; Eduardo L Franco (BMJ Open)
Introduction Human papillomavirus (HPV) is a causal agent of malignancies including cervical, vulvar, vaginal, penile, anal and oropharyngeal cancer, as well as benign conditions such as anogenital warts. HPV vaccination protects individuals against infections with the target HPV types and their clinical outcomes. However, little is known about the protection an immunised individual confers to their sexual partner or its impact on HPV transmission dynamics. In this context, the Transmission Reduction and Prevention with HPV vaccination (TRAP-HPV) study was designed to determine the efficacy of an HPV vaccine in reducing transmission of genital and oral HPV infection in sexual partners of vaccinated individuals.Methods and analysis The TRAP-HPV study is an ongoing randomised controlled trial among heterosexual couples living in Montreal, Canada. Sexually active couples, aged between 18 and 45 years, who have been in a relationship no longer than 6 months are considered eligible. Participants are independently randomised to receive either the intervention HPV vaccine, Gardasil 9, or a placebo hepatitis A vaccine, Avaxim, creating four vaccination groups among couples: intervention–intervention, intervention–placebo, placebo–intervention and the placebo–placebo. Participants provide genital (vaginal/penile) and oral samples at baseline and five follow-up visits over a 1-year duration. Linear Array HPV genotyping is used to detect 36 HPV types. Cox proportional hazard regression models will be used to estimate the effect of vaccination on HPV transmission.Ethics and dissemination The TRAP-HPV study received ethical approval by institutional review boards McGill University, Concordia University and Centre Hospitalier de l’Université de Montréal. Before enrolment, all participants provide informed written consent. Results will be published in peer-reviewed journals and presented at national and international conferences. The generated empirical evidence could be used in mathematical models of vaccination to inform policymakers in Canada and elsewhere.Trial registration number NCT01824537.